The Extent to Which High School Principals Exercise Ethical Leadership And Its Relation to Some Variables Field Study From the Point of View of Teachers in the City of Latakia (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The objective of the research is to identify the level of the practice of secondary school principals in Lattakia for ethical leadership from the point of view of teachers according to the following axes: the administrative qualities of the headmaster, the administrative qualities of the principal, human relations. And to study the differences between the teachers 'estimates of the degree of their managers' conduct of the ethical leadership due to the variables: gender, scientific qualification and the number of years of service. The research was based on a descriptive approach. The research community included all teachers in secondary education in Lattakia. The sample of the research was a random sample of 250 teachers and schools. The survey questionnaire was distributed to them. 233 of them were fully researched and valid for statistical analysis. With a response rate of (93.2%).The results of the study showed that the level of secondary school principals in Lattakia for moral leadership from the point of view of teachers was high. Human relations came first, followed by moral personality traits, followed by moral administrative qualities. The results also showed no statistically significant differences between the teachers 'estimates of their managers' level of ethical leadership according to gender variables, years of service and scientific qualification.